2024
DOI: 10.1371/journal.ppat.1012001
|View full text |Cite
|
Sign up to set email alerts
|

The multiplicity of thioredoxin systems meets the specific lifestyles of Clostridia

Cyril Anjou,
Aurélie Lotoux,
Anna Zhukova
et al.

Abstract: Cells are unceasingly confronted by oxidative stresses that oxidize proteins on their cysteines. The thioredoxin (Trx) system, which is a ubiquitous system for thiol and protein repair, is composed of a thioredoxin (TrxA) and a thioredoxin reductase (TrxB). TrxAs reduce disulfide bonds of oxidized proteins and are then usually recycled by a single pleiotropic NAD(P)H-dependent TrxB (NTR). In this work, we first analyzed the composition of Trx systems across Bacteria. Most bacteria have only one NTR, but organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Possession of three homologs of trxB gene by VITHBRA001 (against one trxB homolog in VITHBRA024) would offer better oxidative stress management. Involvement of multiple Trx system in efficient oxidative stress management has been reported of late in Clostridioides difficile (a Firmicute) [ 181 ].…”
Section: Resultsmentioning
confidence: 99%
“…Possession of three homologs of trxB gene by VITHBRA001 (against one trxB homolog in VITHBRA024) would offer better oxidative stress management. Involvement of multiple Trx system in efficient oxidative stress management has been reported of late in Clostridioides difficile (a Firmicute) [ 181 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cheng et al also indicated that thioredoxin is essential for motility and contributes to host infection of Listeria monocytogenes via redox interactions [ 13 ]. The function of trxB remains a topic of exploration [ 35 , 36 ]. As a crucial component of the thioredoxin system, trxB plays a pivotal role in oxidative stress, virulence modulation, growth regulation, drug resistance, and other essential processes [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%